Pola Komunikasi Komunitas Laskar Sepeda Tua Pekanbaru Dalam Mempertahankan Solidaritas Kelompok - MAHATIR, MUHAMMAD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Communication is a human need to live a life, man can not live without communicating. communication activities always take place from day to day, from time to time for human life and human activity will not be separated from communication. community is one container for the community for hobby interest and share information. In the community all members can deliver the aspirations, and interacting to improve, the existence solidarity between members, and group cohesiveness. The aim of this research are to determine the communication interaction analysis, the flow of communication, as well as communication networks which is conducted Old Bicycle Warriors community Pekanbaru in maintaining solidarity groups.This research uses qualitative method with descriptive approach, and with interview, documentati and observation data collection technique. Data then processed to reduced, thus, arranged to get general conclusion. The research was done in the Old Bicycle Community Warriors Pekanbaru. With the object of research namely communication patterns Old Bicycle Community Warriors Pekanbaru in maintaining group solidarity and subject in this research amounted to 7 peoples based on purposive and accidental methods used by the researcher. Otherwise, checked the legality of data, the researcher uses acceleration participation and triangulation techniques.Research results obtained showed that communication interaction analysis the is conducted Old Bicycle Community Warriors Pekanbaru occurs intensely and continuously when they met and gathered, their purpose communicated is solely to share information and exchange ideas among its members. the flow of communication Old Bicycle Community Warriors Pekanbaru shaped one-way communication and two-way where the one-way communication and two-way occurs at the time of assignment, meet, and communicate face-to-face, while the communication network Old Bicycle Community Warriors Pekanbaru shaped communication patterns all channels, where within a certain meeting face to face or communicate directly all members are free to communicate with anyone as long as they are comfortable and suitable to communicate with each other. With communication patterns like this Old Bicycle Community Warriors Pekanbaru can maintain group solidarity and make this community persisted until today.Keyword: Patterns Of Communications, Solidarity Group, Laskar Sepeda Tua Pekanbaru